Antiplatelet action over the platelet count in platelet-rich plasma. - González, Maczy; Arteaga Vizcaíno, Melvis; Ruiz, Ana; Esis, Daniela; González, Biagney; Rosmary Galue, Ricardo; Fernández, Nelson (Revista Colombiana de Hematología y Oncología, 2013)
Objective: Evaluate the platelet count in the platelets-rich plasma (PRP) from healthy subjects before and after the administration of antiplatelet agents. Material and method: It is studied 32 subjects, 20 female and 12 male, between 18 and 50 years old and apparently healthy. They were distributed in two groups: 1) 16 subjects who received aspirin (100 mg) and 2) 16 with clopidogrel (75 mg), these doses were unique for a day. In each subject is extracted 16,5 ml of venous blood antecubital for platelet count in peripheral blood and PRP, platelet aggregation before treatment is practiced. Results: In all the studied subjects are found a platelet count before treatment with antiplatelet in peripheral blood of 276,55 ± 66,43 x mm3 and 24 hours after 281,38 ± 81,55 x mm3. In the PRP of subjects before to receiving aspirin was 566,86 ± 109,16 x mm3 and then 526,34 ± 90,55 x mm3; prior to clopidogrel ingestion was 444,76 ± 100,65 x mm3 and 388,82 ± 71,94 x mm3 after treatment. Significant differences for the platelet count were found only for clopidogrel (p < 0,05). The correlation for the count of platelets before and after the treatment only exists for aspirin (r = 0,88). Conclusions: In this study showed a significant decrease in the platelet count after administering clopidogrel without correlation between them before and after treatment. Further studies are necessary to evaluate a larger number of cases and their effect on platelet aggregation.